2014
DOI: 10.1080/09297049.2013.876493
|View full text |Cite
|
Sign up to set email alerts
|

The burden and predictors of cognitive impairment among 6- to 8-year-old children infected and uninfected with HIV from Harare, Zimbabwe: A cross-sectional study

Abstract: With long-term survival of children infected with HIV, information on cognitive function at school age is needed. To determine cognitive function among 6- to 8 year-old children exposed to HIV and to assess factors associated with cognitive impairment, we conducted a cross-sectional study from October 2010 to December 2011 among children whose mothers participated in a national HIV prevention program in Harare. Cognitive function was assessed using the McCarthy Scales of Children's Abilities (MSCA). Of the 306… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 47 publications
0
16
0
1
Order By: Relevance
“…However, other studies point to subtle challenges in early language development being the possible effect of in utero exposure to ART use in pregnancy [ 189 , 190 ]. Furthermore, adolescents with HIV infection are frequently exposed to adverse environmental influences including poverty, stress, violence and maternal ill-health, which could also contribute to neurocognitive and psychiatric risk [ 191 , 192 ]. These findings suggest a multifactorial aetiology to neurocognitive and behavioural outcomes among this vulnerable population, and there is the need for further research to ascertain the contributions of these individual risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies point to subtle challenges in early language development being the possible effect of in utero exposure to ART use in pregnancy [ 189 , 190 ]. Furthermore, adolescents with HIV infection are frequently exposed to adverse environmental influences including poverty, stress, violence and maternal ill-health, which could also contribute to neurocognitive and psychiatric risk [ 191 , 192 ]. These findings suggest a multifactorial aetiology to neurocognitive and behavioural outcomes among this vulnerable population, and there is the need for further research to ascertain the contributions of these individual risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations into the neurocognitive functioning of HIV-EU children have produced ambiguous findings. For example, there is some evidence that their neurocognition does not differ from that of neurotypical children (Kandawasvika et al, 2015), while other studies have found significant impairments in verbal functioning, sequencing, memory, and quantitative reasoning (Levenson et al, 1992; Brackis-Cott et al, 2009; Kerr et al, 2014). Kerr et al (2014) compared the neurocognitive functioning of HIV-EU children from Thailand ( n = 160) and Cambodia ( n = 202) to an unexposed control group ( n = 167).…”
Section: Introductionmentioning
confidence: 99%
“…However, despite comparable SES, pHEU children underperform on neuropsychological tests compared with HIV-unexposed children [2,5,23]. The studies using healthy children as controls were mostly from developing countries [2][3][4][5]24] or SESunmatched [11].…”
mentioning
confidence: 99%